Students’ Engagement on English Learning through YouTube Video for Primary Teacher Education Study Program - Isnaini Eddy Saputro (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Synchronous online instruction is a tool to provide learning source for the students and educators in 21st century. YouTube as synchronous online instruction is used not only for entertainment but also in teaching English for students. This research has purpose to explain students’ Engagement in English learning through YouTube channel to deliver their opinion and idea. The data was collected by observing teaching and learning process and students’ engagement checklist. This research used descriptive case study to explain the result. It found that what the lecturer taught through YouTube video, it had given beneficial references for students because the lecturer used YouTube as media in teaching English. Moreover, the students used YouTube video to practice English skills such as they practiced to conversation with friends, discussion, sharing idea, describing and giving opion. Besides that, the students can listen the several videos in YouTube related to the topic. Therefore, it indicated that three aspects of engagement presented on this study such as emotional, cognitive, and behaviour engagement had answered.